D-branes on noncompact Calabi-Yau manifolds: K-theory and monodromy - de la Ossa, X; Florea, B; Skarke, H (2002)
We study D-branes on smooth noncompact toric Calabi-Yau manifolds that are resolutions of Abelian orbifold singularities. Such a space has a distinguished basis S i for the compactly supported K-theory. Using local mirror symmetry we demonstrate that the Si have simple transformation properties under monodromy; in particular, they are the objects that generate monodromy around the principal component of the discriminant locus. One of our examples, the toric resolution of ℂ 3/(ℤ 2 × ℤ 2), is a three parameter model for which we are able to give an explicit solution of the GKZ system. © 2002 Elsevier Science B.V. All rights reserved.